Turismo e megaeventos esportivos - Ishiy, Morupi (Revista Turismo em Análise, 1998)
This paper shows more and more important of sport events in travel and tourism intemational market, their importance to the tourism industry and their impacts in the host places. It treats more specifically of the effects caused by "sport megaevents", through facts happened in some editions of the Summer Olympic Games and the Footbal/ (Soccer) World Cup Championship.